Meningitis with cranial polyneuritis and cavernous sinus thrombosis by Borrelia crocidurae: First autochthonous case in Europe. (May 2019) - Malincarne, Lisa; Schiaroli, Elisabetta; Ciervo, Alessandra; Scaglione, Vittoria; Paciaroni, Maurizio; Mancini, Fabiola; Paglia, Maria Grazia; Cardaci, Salvatore; Pasticci, Maria Bruna; Francisci, Daniela; Baldelli, Franco
Highlights: Autochthonous case of Borrelia crocidurae infection in Europe. Borrelia crocidurae neurotropism. Borrelia crocidurae meningitis with cranial polyneuritis and cavernous sinus thrombosis. Abstract: Borrelia crocidurae is endemic in West Africa, where it represents the leading cause of tick-borne relapsing fever (TBRF). TBRF typically presents with high fever and systemic symptoms, followed by recurrent episodes. Neurological complications may occur during febrile relapses. B. crocidurae is considered the most neurotropic agent of TBRF and is associated to severe neurological manifestations i.e. meningitis and encephalitis. To date, European cases of B. crocidurae infection have been reported in travelers returning from endemic areas. We report the first autochthonous case in Europe of B. crocidurae infection, presenting as meningitis with cranial polyneuritis and cavernous sinus thrombosis that were not preceded by classic febrile recurrences.